Production And Trade Competitive Advantages Of Natural Rubber In India - Pradeep U (Department of Agricultural Economics, College of Horticulture, 2003)
The study entitled Production and Trade Competitive Advantages of Natural Rubber In India" was undertaken with the specific objective of examining the emerging trends in production, consumption, export and import of NR and the to assess the competitive advantages an disadvantages in the specific context of WTO regime. The study was conducted in the year 2001-03, using both primary and secondary data. The trend analysis using different functional forms revealed that a growth functional form was the best fit for tapped area, production and yield of natural rubber whereas the exponential function turned out to be best fit for consumption of natural rubber. An analysis of the composition pattern revealed that natural rubber is slowly replacing the synthetic rubber in the world as well as in the Indian market. The growth rate analysis of the area, tapped area, production and yield of natural rubber and reclaimed rubber revealed that their growth was highest during the sixties. It declined substantially thereafter. More instability was experienced in the production of natural rubber during the eighties and the nineties. The decomposition analysis revealed that the price effect was a major contributing factor in the growth of natural rubber output in India. There was considerable production advantage for NR producers in India with the average market price being consistently higher than the cost of production. There was no comparative advantage for natural rubber production in India for international trade as revealed by the domestic resource cost ratio. The Nominal Protection Coefficients indicated that Indian natural rubber was not enjoying trade competitive advantage in the international market. The bound rate for natural rubber is now fixed at 25 per cent instead of 100 per cent for primary agricultural commodities because it is classified as an 'industrial raw material" under the WTO agreements. No "surge in imports" consequent to the removal of quantitative restrictions in natural rubber was